(untitled) (American Journal of Islam and Society, 2009)
Books Reviewed: Kamal Boullata and Kathy Engel, eds. We Begin Here: Poems for Palestine and Lebanon. Northampton, Massachusetts: Interlink, 2007; Nadia G. Yaqub. Pens, Swords, and the Springs of Art: The Oral Poetry Dueling of Palestinian Weddings in the Galilee. Leiden and Boston: Brill, 2007; Laleh Khalili. Heroes and Martyrs of Palestine: The Politics of National Commemoration. New York: Cambridge University Press, 2007. The Israeli-Palestinian conflict, which hasmade headlines for decades, shows no sign of abating, for each side is convinced that it is in the right and demands to live upon its ancestral land. The Palestinian “problem,” which has produced a plethora of books, goes back to Israel’s 1948war of independence and remains unresolved. In this essay, I shall review two books that deal directly with the Palestinian problem and their overall situation (especially of the Palestinian refugees in Lebanon) and one on oral poetic duels among Palestinians in Israel. This latter book provides some between-the-lines insights about how Israeli Arabs cope with the Palestinian problem ...